2015
DOI: 10.1038/srep14966
|View full text |Cite
|
Sign up to set email alerts
|

Self-transport and self-alignment of microchips using microscopic rain

Abstract: Alignment of microchips with receptors is an important process step in the construction of integrated micro- and nanosystems for emerging technologies, and facilitating alignment by spontaneous self-assembly processes is highly desired. Previously, capillary self-alignment of microchips driven by surface tension effects on patterned surfaces has been reported, where it was essential for microchips to have sufficient overlap with receptor sites. Here we demonstrate for the first time capillary self-transport an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
3
17
1
Order By: Relevance
“…The experimental setup had a relative humidity above 90% and the temperature was maintained at 24 C throughout the experiments. The size of the droplets in this case typically ranges from 1 to 5 mm in diameter, 59 which is similar to those reported elsewhere 38 and comparable to that of atmospheric fog. Then, the volume of water was collected and measured with a weight balance at intervals of 20 min over a period of 2 h. For the onset of dripping experiments, the surfaces used were 15 mm  15 mm in dimensions and were freshly and independently fabricated.…”
Section: Fog Collection Experimentssupporting
confidence: 88%
“…The experimental setup had a relative humidity above 90% and the temperature was maintained at 24 C throughout the experiments. The size of the droplets in this case typically ranges from 1 to 5 mm in diameter, 59 which is similar to those reported elsewhere 38 and comparable to that of atmospheric fog. Then, the volume of water was collected and measured with a weight balance at intervals of 20 min over a period of 2 h. For the onset of dripping experiments, the surfaces used were 15 mm  15 mm in dimensions and were freshly and independently fabricated.…”
Section: Fog Collection Experimentssupporting
confidence: 88%
“…Compared to the single droplet methods, the parallel stochastic methods can produce a huge amount of individual droplets of down to femtoliter volumes, which makes it highly efficient. The parallel stochastic method is most suitable for water disposition, 54,92,96 even though other liquids can also be handled. As the deposition takes place on the full substrate, droplets on undesired regions of the substrate (e.g., outside the receptors) should be removed by post-processing (e.g., vaporization) after the self-alignment step, unless their existence is compatible with the subsequent processing steps.…”
Section: Process Integrationmentioning
confidence: 99%
“…Particularly, self-transport and self-alignment of microcomponents was reported, whereby even a gap of tens of microns between a component and its shape-matching receptor, defined chemically on a superhydrophobic substrate, is bridged by means of microscopic rain. 96…”
Section: Component Feedingmentioning
confidence: 99%
“…Several other reported methods for self-assembly use the surface tension in combination with either solder bumps [5][6][7] , magnetic [8,9] or electrophoretic [10,11] forces, or capillary transport. [12] Smith et al and Jacob et al [13] have reported higher yields for the assembly process in their works.…”
Section: Introductionmentioning
confidence: 99%